The contribution of field efficacy studies to the evaluation of applications for veterinary vaccines evaluated through the European Union centralised authorisation procedure. (April 2021) - Mackay, David; Jimenez, Cristina Martin; Ioannou, Faye; Ilott, Martin
Abstract: To examine the contribution that field efficacy studies made to the assessment of marketing authorisation (MA) applications, a retrospective analysis was conducted for 100 veterinary vaccines that had been evaluated by the European Medicines Agency (EMA) between 1996 and 2017. For 52 veterinary vaccines, scrutiny of the European Public Assessment Report (EPAR) and/or the summary of product characteristics (SPC) identified objective evidence that field efficacy studies made an important or substantial impact on the efficacy claims and/or benefit-risk evaluation. For 24 applications, the contribution of field efficacy studies was classified as either supportive or was not detectable from the publicly available documents on which the analysis was based. For a further 24 applications, data exemptions were applied and the MAs were granted in the absence of field studies. The difficulty in achieving challenge in the field was highlighted by the observation that natural exposure was reported in less than half of the applications where field efficacy studies were conducted (34 out of 76). This analysis may help to inform policy decisions on the role, conduct and contribution that field efficacy studies make to the assessment of efficacy for veterinary vaccines.